DEVELOPING CHILDREN'S COMMUNICATION ABILITY THROUGH OF STORY METHOD USING HAND PUPPET MEDIA: MENGEMBANGKAN KEMAMPUAN BERKOMUNIKASI ANAK MELALUI METODE BERCERITA DENGAN MEDIA HAND PUPPET - DWI RENNY HIDAYATI; ERVIN NURUL AFFRIDA (incrementapedia, 2020)
The problem in this study is about learning media that are not maximal in the process and activities in class. This study aims to determine the communication skills of children by applying the method of telling stories using hand puppet media in group a children in early childhood education. The subjects of this study were the Group A2 totaling 18 children. The type and research approach used in this study are quantitative pre-experimental methods, using one group pretest-posttest. From the results of this study concluded that the value of t arithmetic = 3.72 is greater than t table 1.739 with a significance level of 0.05% and 2.556 at a significance level of 0.01 with N = 18 which means the naught hypothesis (Ho) is rejected and the working hypothesis (Hl) is accepted. This proves that the working hypothesis (Hl) which states "there is a positive influence on the hand puppet media on children's communication skills is accepted.